Prospective comparative study of mesh fixation in laparoscopic TEP hernia repair using tacker versus cyanoacrylate versus fibrin glue tep mesh fixation with cyanoacrylate - Shukla, Arvind; Kalsi, Meher; Yogesh Shivaprasad ,; Shah, Srashti; Ahirwar, Tanuj; Sharma, Aditi (Asian Journal of Medical Sciences, 2022)
Background: Laparoscopic inguinal hernia repairs done by totally extra peritoneal (TEP) or trans abdominal preperitoneal techniques require mesh fixation which is commonly done by either tackers or fibrin glue. In this study, we discuss about using cyanoacrylate glue for mesh fixation as a more cost effective but equally suitable alternate. Aims and Objectives: The aim of the study was to evaluation of suitability of using highly economical cyanoacrylate ($ 0.13) with tackers ($ 318.52) and fibrin glue ($ 11.94) for mesh fixation during TEP hernia repair. Materials and Methods: A comparative study was done in the Department of Surgery over a period of 3 years (2018–2021). This study included 210 patients who underwent laparoscopic TEP hernia repair. Cases were randomized into three groups of 70 subjects each: Group A - mesh was fixed with tacker, Group B - mesh was fixed using cyanoacrylate, and Group C - mesh was fixed with fibrin glue. Subjects were followed up for 3 months. Type of presentation, diagnosis, and type of mesh fixation were compared to post-operative complications that included pain, seroma, hematoma, and urinary retention findings were recorded and data were statistically analyzed using “SPSS” software. Results: Decreased incidence of post-operative pain (P=0.01) and hematoma was observed in Group B as compared to Groups A and C. Average hospital stay was significantly less in fibrin glue group (P=0.02) and cyanoacrylate group (P=0.02) as compared to tacker group. There was same incidence of postoperative urinary retention (P=0.520) and seroma (P=0.354) formation between all groups. Patients of Group B started daily activities earlier at 15 days follow-up (P=0.032) as compared to Groups A and C. Conclusion: Cyanoacrylate and fibrin glue fixation of mesh in laparoscopic TEP have better outcomes when compared to tackers. Furthermore, as cyanoacrylate is 300 times cheaper than tacker and 10 times cheaper than fibrin glue, this imparts a huge cost advantage to this technique in developing countries. Therefore, use of cyanoacrylate for mesh fixation in laparoscopic TEP can be safely advocated over tackers and fibrin glue.